On the non‐thermal plasma synthesis of nickel nanoparticles. Issue 1 (23rd August 2017) - Woodard, Austin; Xu, Lihua; Barragan, Alejandro A.; Nava, Giorgio; Wong, Bryan M.; Mangolini, Lorenzo
Abstract : Nickel (Ni) nanoparticles have been synthesized from the dissociation of nickelocene (Ni(Cp)2 ) in an argon‐hydrogen (Ar‐H2 ) low pressure continuous‐flow non‐thermal plasma. The influence of process parameters on the synthesized Ni nanomaterial structure, size, size‐dispersion, and carbon content has been characterized by EDS and TEM analysis. The role of hydrogen dilution and plasma input power on material throughput is carefully discussed. These data, in combination with the prediction of the electron affinity and ionization potential of Ni(Cp)2 by DFT calculations, supports the hypothesis that the material loss‐mechanism to the reactor walls is due to the inherent ambipolar diffusion present in this synthesis technique. This study suggests that precursors should be screened with care when attempting to produce nanoparticle via a low pressure, continuous flow plasma reactor. Abstract : On the non‐thermal plasma synthesis of nickel nanoparticles . The correlation between the processing parameters, the plasma chemistry, and resulting nanomaterials properties is investigated.